THE EFFECT OF ONLINE LEARNING ON STUDENTS’ WRITING CREATIVITY IN WRITING DESCRIPTIVE TEXT ABOUT LOCAL TOURISM - Irma Khoirot Daulay; Ekrina Lidwina br Ginting; Febri Oktavia Manik; Wulan Siringo-ringo; Hotlina Sitohang (Universitas Islam Sumatera Utara, 2021)
As a result of the pandemic, the best alternative to support formal learning activities is online learning, and it is believed to affect students' creativity in writing. The research aims to discover the effect of online learning on students' creativity in writing descriptive texts about local tourism. The methodology used by researchers in this research is a true-experimental method with a quantitative approach. This study uses a type of post-test-only control class design. There are two clases in this experiment design, each selected randomly. After conducting the study, researchers found a significant difference in grades between classes that received online learning treatment (experimental classes) and classes that were not (Control classes), where the experimental class scores were higher than the control class. So, the conclusion is that online learning has a good Effect on students' creativity in writing descriptive texts about local tourism.